KKT Solution and Conic Relaxation for Solving Quadratically Constrained Quadratic Programming Problems - Lu, Cheng; Fang, Shu-Cherng; Jin, Qingwei; Wang, Zhenbo; Xing, Wenxun (SIAM journal on optimization, 2011)
To find a global optimal solution to the quadratically constrained quadratic programming problem, we explore the relationship between its Lagrangian multipliers and related linear conic programming problems. This study leads to a global optimality condition that is more general than the known positive semidefiniteness condition in the literature. Moreover, we propose a computational scheme that provides clues of designing effective algorithms for more solvable quadratically constrained quadratic programming problems. [PUBLICATION ABSTRACT]